The mosquito crusades : a history of the American anti-mosquito movement from the Reed Commission to the first Earth Day - Patterson, Gordon M. (Studies in modern science, technology, and the environment., 2009)
Among the struggles of the twentieth century, the one between humans and mosquitoes may have been the most vexing, as demonstrated by the long battle to control these blood-sucking pests. As vectors of diseases such as malaria, yellow fever, encephalitis, and dengue fever, and as sources of torment, mosquitoes forced open a new chapter in the history of medical entomology and human attempts to suppress the insect world. Based on extensive use of primary sources, The Mosquito Crusades traces efforts to eliminate the mosquito blight from the New Jersey Meadowlands to San Francisco Bay. Providing.